Social Media Adoption and Business Performance: A Study of Student Entrepreneurial Small Businesses - Purmono, Bintoro Bagus; Syahlidi, Goku; Videlya, Viola; Meliani, Dwi Rosita (Jurnal Mebis, 2025)
SMEs managed by students as entrepreneurs play a role in pushing innovation, growing economy, and creating fieldwork in the community. Students often have a better understanding of technology and trends, which allows them to utilise opportunities overlooked by older generations. One of the method, students use technology and trends through social media adoption in businesses. Research aims to study the influence of social media adoption on the performance of student entrepreneurial small businesses. The research method used is Structural Equation Modelling (SEM) with the help of AMOS statistics to test the connection between the independent and dependent, supporting the hypothesis proposed. Data were collected through a questionnaire with 220 respondents consisting of student entrepreneurs who have been operating a business for at least 1 year and adopting social media. The results show that social media adoption is influential and significant to the performance of student entrepreneurial small businesses.